Wegbreit: a cautionary tale for trustees, lawyers and wealth owners. Issue 2 (22nd January 2020) - Hunter, Chelsea; Gifford, James
Abstract: On 8 July 2019, the US Tax Court held that a grantor trust holding offshore life insurance constituted a sham. A review of the facts of the case and the court's opinion offer a cautionary tale to those planning, maintaining, or benefitting from similar wealth-holding structures. Like most cautionary tales, this one blends a unique factual milieu with tragic decision-making. But, unlike most cautionary tales, this one helps to illustrate some fundamental tax and wealth structure planning points.